2012
DOI: 10.1158/0008-5472.can-12-1383
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible miR-210 Regulates the Susceptibility of Tumor Cells to Lysis by Cytotoxic T Cells

Abstract: Hypoxia in the tumor microenvironment plays a central role in the evolution of immune escape mechanisms by tumor cells. In this study, we report the definition of miR-210 as a miRNA regulated by hypoxia in lung cancer and melanoma, documenting its involvement in blunting the susceptibility of tumor cells to lysis by antigen-specific cytotoxic T lymphocytes (CTL). miR-210 was induced in hypoxic zones of human tumor tissues. Its attenuation in hypoxic cells significantly restored susceptibility to autologous CTL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
127
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(131 citation statements)
references
References 44 publications
4
127
0
Order By: Relevance
“…Moreover, some diagnostic miRNAs can be used in therapy. For instance, in previous studies, miR-155, which is downregulated in melanoma, was injected in melanoma cell lines to increase its expression (1,21,22). Similar procedures can be executed for miR-193b as a practical therapeutic option (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some diagnostic miRNAs can be used in therapy. For instance, in previous studies, miR-155, which is downregulated in melanoma, was injected in melanoma cell lines to increase its expression (1,21,22). Similar procedures can be executed for miR-193b as a practical therapeutic option (1).…”
Section: Discussionmentioning
confidence: 99%
“…This gene modifies the cell surface of melanoma cells and affects cellular adherence; metastasis occurs due to discontinuity of cancerous cells. Therefore, miR-30b and miR-30 are accountable for metastasis in melanoma (1,21,22).…”
Section: Immunosuppressive Mirnasmentioning
confidence: 99%
“…Increasing evidence, accumulated using microarray technology, has indicated a number of miRNAs that are differentially expressed in response to hypoxia. For example, miRNA-210, -155, -372/373 and -10b were shown to be upregulated, whereas miR-20b and -200b were found to be downregulated in response to hypoxia (5)(6)(7)(8). A recent study suggested that miRNA-150, a Hypoxia promotes C-X-C chemokine receptor type 4 expression through microRNA-150 in pancreatic cancer cells JIN-SHAN SUN 1* , XIAO-LAN ZHANG 2* , YU-JIE YANG 3* , ZHAN-GUO NIE 1 and YONG ZHANG hypoxia-sensitive miRNA, is involved in cancer metastasis via regulation of its target genes (9).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that miR-210 plays an important role in regulation of cell growth, angiogenesis, invasion and apoptosis in different human tumour models [5,11]. MiR-210 expression is frequently up-regulated in a variety of solid tumours, including breast cancer [12], non-small cell lung cancer [29], head and neck cancer [8], pancreatic cancer [4], oral tumours [31], hepatocellular cancer (HCC) [42], adrenocortical carcinoma (ACC) [23], glioblastoma [26], colon cancer [24], ovarian cancer [9], malignant melanoma [22] and renal cell cancer [27]. The expression of miR-210 is found to be down-regulated in human esophageal squamous cell carcinoma (ESCC) tissues and derived cell lines [34].…”
mentioning
confidence: 99%